Re-examining the costs of sanctions and sanctions threats using stock market data. Issue 5 (2nd September 2020) - Webb, Clayton
ABSTRACT: Are sanctions and sanctions threats costly for the sanctioning state? The costs of sanctions for the sender are an important feature of many theories developed to explain the use and utility of economic sanctions. Despite the prominence of this assumption in existing research, there are only a handful of studies that have endeavored to analyze or estimate the economic consequences of sanctions for sender states. This paper builds a theoretical framework that connects the costs of sanctions for sender firms with a phenomenon that can be observed, stock market data. Sanctions and sanctions threats should create market uncertainty that is reflected in stock price volatility for firms with commercial interests in targeted states. Comparisons are made using stock price data for firms within sectors at the same point in time, within sectors over time, and across sectors over time. The stock prices for firms with commercial interests in targeted states are more volatile than stock prices for comparable firms without commercial interests in targeted states. These spells of uncertainty not only reflect the costs of sanctions and sanctions threats for firms caused by interruptions in commercial activities but represent important costs for firms in-and-of themselves.